Practice guidelines in anesthesia - Malhotra, S.K (Jaypee Brothers Medical Publishers, 2016)
The specialties of anesthesia, intensive care and pain management are becoming dynamic facets in the field of medicine. Continuous advancement is being made in improving the quality care of patients undergoing surgical procedures. Practice Guidelines in Anesthesia is an integral component that provides basic recommendations for anesthetic practice. The Indian College of Anaesthesiologists (ICA) that is an academic branch of Indian Society of Anaesthesiologists has come out with the first edition of Practice Guidelines in Anesthesia. The various chapters include the topics covering preoperative preparations, monitoring, intra- and postoperative problems and their management. It also covers the chapters dealing with pain management and the field of intensive care therapy. All the chapters have been meticulously selected and authored by distinguished clinicians.